KEBAYA: Digital Comics on Indonesian Cultural Diversity to Enhance High-Order Thinking Skills in Elementary School - Ismiyanti, Yulina; Fatmawati, Sima; Sari, Yunita; Jupriyanto, Jupriyanto; Enfesta, Lolita; Khosa, Martha (Universitas Muhammadiyah Surakarta, 2025)
In the era of globalisation and digital transformation, elementary education faces challenges in preserving local cultural values within technology-based learning environments. Digital learning media often emphasise globalised content, limiting culturally grounded learning experiences. Meanwhile, Higher-Order Thinking Skills (HOTS) have become a core objective of 21st-century education, yet empirically validated media integrating Indonesian cultural diversity with HOTS development remain scarce. This study aims to develop and evaluate KEBAYA (Digital Comics on Indonesian Cultural Diversity), a culture-based digital comic designed to enhance students’ HOTS through interactive narratives. Using a research and development approach with the ADDIE model, the study involved needs analysis, product design aligned with curriculum and cultural values, development using the Canva application, expert validation, and field trials with elementary students. Effectiveness was assessed through HOTS-oriented tests and response questionnaires. The results show that KEBAYA is valid, practical, and effective in improving students’ HOTS, particularly analysis, evaluation, and creative thinking, offering a scalable model for culturally responsive digital learning. This study contributes to culturally responsive digital pedagogy and provides a scalable learning medium for elementary education.